Dual wavelength high power double-clad erbium/ytterbium-doped fiber laser - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Shahi, S.; Ahmad, Harith (2011)
A dual wavelength high power double-clad erbium/ytterbium-doped fiber laser with a narrowest spacing of 0.4 nm and a M-2 value of close to unity is presented in the region of 1565 nm. This result can be realized with a significant improvement of the mode competition problem using a loop mirror as a comb filter. The wavelength region can also be varied using polarization controllers in the loop mirror. This dual-wavelength fiber laser with side mode suppression ratio (SMSR) of 40 dB is quite stable, and the output power variance is as low as 0.46 dB.